Upaya Meningkatkan Motorik Halus Pada Anak Melalui Kegiatan Melukis Pada Kelompok A Di Tk 02 Kaling Tasikmadu Karanganyar Tahun Pelajaran 2014/2015 - SARI, ANDRI PUSPITA, Drs. Hasto Daryanto, M.Pd, Wiji Astuti, s. Pd., M.Hum (2015)
Painting is an easy way for children to learn. But the use of media to paint for kindergarten (TK) is simple and less innovative, so the fine motor skills of children still low. Media candle is one alternative way media in painting to improve fine motor skills in children. This research purposes to improve fine motor skills in children through the medium of wax on a group of children in kindergarten 02 Kaling. The type of research Class Action Research (PTK) with two cycles of work procedures, consists of four stages. The subjects were teachers and kindergarten children in group A at 02 Kaling Tasikmadu Karanganyar. Results of this study indicate candles media can improve the ability to paint. Results are given a percentage of the prior action until the second cycle is prasiklus 44.84%, 54,99% first cycle ie, the second cycle is %. The conclusion of this study is an increase in the fine motor skills of children through the medium of wax in kindergarten 02 Kaling Academic Year 2014-2015.